Can a mechanical circulatory support comprehensive approach to cardiogenic shock at referral centers reduce 30-day mortality? - Pieri, Marina; Iannaccone, Mario; Burzotta, Francesco; Botti, Giulia; Aurigemma, Cristina; Trani, Carlo; Ajello, Silvia; Altizio, Savino; Sanna, Tommaso; Romagnoli, Enrico; Paraggio, Lazzaro; Cappannoli, Luigi; et al. (Frontiers in Cardiovascular Medicine, 2025)
Although mortality risk prediction in cardiogenic shock (CS) is possible, assessing the impact of the multitude of therapeutic efforts on outcomes is not straightforward. We assessed whether a temporary mechanical circulatory support comprehensive approach to the treatment of CS may reduce 30-day mortality as compared to expected mortality predicted by the recently proposed Cardiogenic Shock Score (CSS). Consecutive CS patients supported by pVAD Impella (Abiomed, Danvers, MA) at two national referral centers were included. 170 patients were included: age was 65 ± 13 years, and 75.9% were male and acute myocardial infarction was the prevalent cause of shock (71.1%). Expected mortality according to CSS was higher than observed (51.8% vs. 41.5%, p < 0.001), this trend being particularly evident for CSS > 4. The AUC ROC curve confirmed poor diagnostic accuracy in this population (AUC 0.53 CI: 0.23–0.82, p = 0.83). The lower observed mortality compared to the expected mortality in critical cardiogenic shock population underscores the role of a comprehensive approach to acute cardiac care patients at referral centers, which should consider including temporary mechanical circulatory support.